2019
DOI: 10.1002/mar.21276
|View full text |Cite
|
Sign up to set email alerts
|

Digital buying behavior: The role of regulatory fit and self‐construal in online luxury goods purchase intentions

Abstract: Drawing on regulatory focus theory, this study examines how consumers’ promotion and prevention focus influences luxury purchase intentions in an online domain. The research further investigates the interactive effects of regulatory focus, goal orientation, and self‐construal through four studies. Study 1 shows that promotion‐focused versus prevention‐focused consumers have a greater tendency to purchase luxury goods online and in‐store. Contrary to extant research regarding the compatibility between message f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…86 MTurkers (43.0% female; M age = 44.35, SD = 12.60) were randomly assigned into either prevention-focused condition or promotion-focused condition (see Appendix 3). They then answered two manipulation check items for regulatory focus on a 7-point Likert scale (see Appendix 2; Fazeli et al, 2019). Results revealed that respondents in prevention-focused situation perceived the negative outcomes more strongly than their counterparts in promotion-focused situation (M = 5.89 vs. 3.14, t(84) = 6.752, p < .001), while respondents exposed to promotion-focused message reported stronger perceived positive outcomes than those exposed to prevention-focused message (M = 5.39 vs. 2.54, t(84) = 7.535, p < .001).…”
Section: Pre-testmentioning
confidence: 99%
“…86 MTurkers (43.0% female; M age = 44.35, SD = 12.60) were randomly assigned into either prevention-focused condition or promotion-focused condition (see Appendix 3). They then answered two manipulation check items for regulatory focus on a 7-point Likert scale (see Appendix 2; Fazeli et al, 2019). Results revealed that respondents in prevention-focused situation perceived the negative outcomes more strongly than their counterparts in promotion-focused situation (M = 5.89 vs. 3.14, t(84) = 6.752, p < .001), while respondents exposed to promotion-focused message reported stronger perceived positive outcomes than those exposed to prevention-focused message (M = 5.39 vs. 2.54, t(84) = 7.535, p < .001).…”
Section: Pre-testmentioning
confidence: 99%
“…Additionally, luxury goods provide emotional and social value to their buyers which differentiates it from nonluxury goods (Vigneron and Johnson, 1999;Tsai, 2005). Therefore, it is important to study the factors affecting online luxury Online luxury purchase intention 585 consumption as they may significantly vary from online shopping motives for nonluxury goods (Liu et al, 2013;Fazeli et al, 2019). Asian countries such as China and India are emerging as the next big market for online luxury sales.…”
Section: Introductionmentioning
confidence: 99%
“…Message framing (Chang et al, 2015;Fazeli et al, 2019) In the scenario, the sign was particularly focused on what would be GAINED if taking part in the ugly food promotion program (1 = strongly disagree, 7 = strongly agree)…”
Section: Normative Influencementioning
confidence: 99%